A Note on Costly Sequential Search and Oligopoly Pricing - Maarten C.W. Janssen; Jose Luis Moraga-Gonzalez; Matthijs R. Wildenbeest (Tinbergen Institute, 2004)
We modify the paper of Stahl (1989) [Stahl, D.O., 1989. Oligopolistic pricing with sequential consumer search. American Economic Review 79, 700–12] by relaxing the assumption that consumers obtain the first price quotation for free. When all price quotations are costly to obtain, the unique symmetric equilibrium need not involve full consumer participation. The region of parameters for which non-shoppers do not fully participate in the market becomes larger as the number of shoppers decreases and/or the number of firms increases. The comparative statics properties of this new type of equilibrium are interesting. In particular, expected price increases as search cost decreases and is constant in the number of shoppers and in the number of firms. Welfare falls as firms enter the market. We show that monopoly pricing never obtains with truly costly search.
Keywords: C13; D40; D83; L13; 330; sequential consumer search; oligopoly; price dispersion; Informationskosten; Oligopol; Suchtheorie